External stimulation: A potential therapeutic strategy for tendon-bone healing - Fu, Shijie; Lan, Yujian; Wang, Guoyou; Bao, Dingsu; Qin, Bo; Zheng, Qiu; Liu, Huan; Wong, Vincent Kam Wai (Frontiers in Bioengineering and Biotechnology, 2023)
Abstract: Injuries at the tendon-bone interface are very common in the field of sports medicine, and healing at the tendon-bone interface is complex. Injuries to the tendon-bone interface can seriously affect a patient's quality of life, so it is essential to restore stability and promote healing of the tendon-bone interface. In addition to surgical treatment, the healing of tendons and bones can also be properly combined with extracorporeal stimulation therapy during the recovery process. In this review, we discuss the effects of extracorporeal shock waves (ESWs), low-intensity pulsed ultrasound (LIPUS), and mechanical stress on tendon-bone healing, focusing on the possible mechanisms of action of mechanical stress on tendon-bone healing in terms of transcription factors and biomolecules. The aim is to provide possible therapeutic approaches for subsequent clinical treatment.